Boosting the oxygen evolution electrocatalysis of high-entropy hydroxides by high-valence nickel species regulation. Issue 55 (22nd June 2022) - Zhang, Tao; Meng, Yu-Lan; Zhao, Yu-Hang; Ni, Jing-Chang; Pan, Yu; Dai, Yan; Tan, Zhenquan; Wang, Xiao-Feng; Song, Xue-Zhi
Abstract : An amorphous NiCoFeCrMo-based high-entropy hydroxide possesses the maximum content of high-valence Ni 3+ species, boosting the oxygen evolution electrocatalytic performance. Abstract : The addition of an extra metal source induces the transformation from crystalline α-Ni(OH)2 to an amorphous NiCoFeCrMo-based high-entropy hydroxide (HEH) and maximizes the high-valence Ni 3+ content in HEH. For OER electrocatalysis, the quinary HEH possesses an overpotential of 292 mV at 10 mA cm −2, a Tafel slope of 54.31 mV dec −1 and the boosted intrinsic activity, surpassing other subsystems.